Effect of Intrinsic and Extrinsic Factors of Choosing Study Majoring on Career Satisfaction: A Mediating Role of Career Path - Muhammad Donal Mon; Lidyana Octavia (Universitas Padjadjaran, 2023)
The research aims to study the factor that affects an individual in choosing a major of study to career satisfaction mediated by a career path in Batam city. This research uses the variable of parental support, intrinsic motivation and extrinsic motivation as the independent variable, career path as the mediation variable and career satisfaction as the dependent variable. The study uses the purposive sampling method. Two hundred fifty respondents in this research are residents of Batam. The data were processed using Partial Least Square (PLS) Software. The results of this study show that the process of choosing a major of study influence career satisfaction. Variables of parental support and intrinsic and extrinsic motivation significantly influence the career path. Intrinsic and extrinsic motivation substantially affect the career satisfaction mediated by career path, except for the parental support variable. Intrinsic and extrinsic motivation significantly influence career satisfaction, except for the parental support variable. Career path as the mediation variable significantly influences career satisfaction.